O DESENVOLVIMENTO DOS CURSOS DE FORMAÇÃO DE PROFESSORES PRIMÁRIOS NA FRONTEIRA OESTE PARANAENSE: a criação da primeira Escola Normal Secundária pública de Foz do Iguaçu e do Oeste do Paraná - Sbardelotto, Denise Kloeckner (2009)
This research has as investigative aim the development of the ordinary public courses to graduate primary teachers in the current mesoregion west of the State of Paraná, more specifically in the urban pioneer area of Foz do Iguaçu. We began from the following problematic: Which political and economic determiners led to the development of teachers´ graduation courses in the West of Parana? The historical approach is defined within the years of 1946, when the Organic Law of Normal Education was issued, and 1960, year when the first Normal Education finished their studies. The main objective is to analyze the economical, political and educational aspects which determine the development of teachers´graduation courses, until the creation of the Normal Secondary School “Iguaçu”. The study starts presenting the organization of public primary school and the Normal Public Courses of teachers´ graduation in Brazil and in the State of Paraná, as well as the influence of the work conceptions and teaching graduation of Erasmo Pilotto in the policies regarding teaching graduation, linked to the principles of Movement for New School. After that, it presents some aspects which might be relevant in relation to the process of occupation of the current mesoregion west of the State of Paraná, to the development of public primary education and the demand for skillful teachers. Finally, the political, economical and educational aspects are presented, those which determined the development of the first initiatives in graduating teachers in the mesoregion west of Paraná, until the creation of the Normal Secondary School “Iguaçu”. The theoretical-methodological reference adopted in the development of the research and analysis of the sources is based on the dialectic historical materialism. Four (04) interviews were made with ex-normalists and one (01) interview was made with one of the first principals of the referred Normal School, and they could tell how the development of teachers´ graduation courses in the West of Parana occurred. The study determined that the normal public primary courses in the West of Paraná, started from the decade of 1950s with the implementation of the Regional Normal Courses and its subsequent Secondary Normal School “Iguaçu”, although it had made possible the expansion of the number of skillful teaches in the region, it represented otherwise the diffusion of the urban-industrial social life sample, necessary to the adequacy of the region to the new demands of the capitalist context. While the Regional Normal Courses were created because of the necessity of the settlers for skillful teachers, the Secondary Normal School was created as a result of the claim of the upper class in Foz do Iguaçu, eager for a graduation in secondary level which made possible the maintenance of its economical and cultural hegemony, through the occupation of educational leading roles. Therefore, while the Regional Normal Courses kept forming teachers for the isolated schools aimed to the working class, Secondary Normal School graduated teachers provenient from the dominant class, mainly interested in be part of the educational leading roles in Foz do Iguaçu and west of Paraná.